Pharmacokinetics and Pharmacodynamics of Edivoxetine (LY2216684), a Norepinephrine Reuptake Inhibitor, in Pediatric Patients with Attention-Deficit/ Hyperactivity Disorder - Kielbasa, William; Quinlan, Tonya; Jin, Ling; Xu, Wen; Lachno, D. Richard; Dean, Robert A.; Allen, Albert J. (Journal of child and adolescent psychopharmacology, 2012)
Edivoxetine (LY2216684) is a selective and potent norepinephrine reuptake inhibitor (NERI). The pharmacokinetics (PK) and pharmacodynamics (PD) of edivoxetine were assessed in children and adolescent patients with attention-deficit/hyperactivity disorder (ADHD) following single and once-daily oral doses of edivoxetine. During a phase 1 open-label safety, tolerability, and PK study, pediatric patients were administered edivoxetine at target doses of 0.05, 0.1, 0.2 and 0.3 mg/kg, and blood samples were collected to determine plasma concentrations of edivoxetine for PK assessments and plasma 3,4-dihydroxyphenylglycol (DHPG) concentrations for PD assessments. Edivoxetine plasma concentrations were measured using liquid chromatography with tandem mass spectrometric detection, and DHPG was measured using liquid chromatography with electrochemical detection. Edivoxetine PK was comparable between children and adolescents. The time to maximum concentration (t(max)) of edivoxetine was ∼2 hours, which was followed by a mono-exponential decline in plasma concentrations with a terminal elimination half-life (t(1/2)) of ∼6 hours. Dose-dependent increases in area under the edivoxetine plasma concentration versus time curve from zero to infinity (AUC(0-∞)) and maximum plasma concentration (C(max)) were observed, and there was no discernable difference in the apparent clearance (CL/F) or the apparent volume of distribution at steady state (V(ss)/F) across the dose range. In adolescents, edivoxetine caused a maximum decrease in plasma DHPG concentrations from baseline of ∼28%, most notably within 8 hours of edivoxetine administration. This initial study in pediatric patients with ADHD provides new information on the PK profile of edivoxetine, and exposures that decrease plasma DHPG consistent with the mechanism of action of a NERI. The PK and PD data inform edivoxetine pharmacology and can be used to develop comprehensive population PK and/or PK-PD models to guide dosing strategies.